WORKPLACE CONSEQUENCES OF WORK-FAMILY CONFLICT FOR WOMEN - Okolie, Ugo Chuks; Uwayah, Lydia I. (LPPM Universitas Malikussaleh, 2024)
Traditional gender roles state that women should prioritize caring for their families and maintaining their homes, while men should prioritize their work. The number of couples balancing two careers has steadily increased over the last few decades. Married women who work put in more hours taking care of their kids and taking care of the house than their working husbands. Traditional women's roles have changed over time, but they still reflect a one-way relationship between work and family. Women have a harder time juggling the demands of family and work. Women find it more difficult to give up their family responsibilities, even when they are employed. It is against this backdrop that this study examined the implications of work-family conflict for women at the workplace. This study is theoretical in nature and relied on context analysis. The study concluded that both work-family conflict and family-work conflict had positive relationships with job tension and the number of hours worked, and both types of conflict had negative relationships with organizational commitment, job satisfaction, life satisfaction, and turnover intention. The lack of sensitive, responsive, and consistent care from overworked parents or substitute providers can lead to decreased cognitive and social skills and can promote attachment insecurity in children, research is still unclear about the effects this time sacrifice may have on children. Therefore, flexibility in the workplace is necessary to reduce distress, including changes in appetite, aches and pains related to tension, and difficulty falling and staying asleep in women.